TANGGUNG JAWAB HUKUM PT GRAB TEKNOLOGI INDONESIA TERHADAP KONSUMEN TENTANG KUALITAS MAKANAN DAN PELAYANAN PENGIRIMAN GRABFOOD - Rildo Rafael Bonauli, (2020)
Transportation or transportation is a very important means of life for the Indonesian people. Transportation or transportation is also very useful for the smooth running of the economy, strengthening unity and integrity and smoothing relations with other countries. As a vast archipelagic country, air, land and sea transportation is an inevitable choice. Online transportation at present, according to the author, has a good influence on the community, but the existence of online transportation also raises pros and cons, both for the delivery of food and the quality of food sold. In connection with this, this thesis raises two problems, namely First, regarding online transportation regulations in the delivery and quality of food and goods in Indonesia and secondly the legal responsibility given if there is a loss in the form of damage, loss, consumer complaints in the process of organizing grab food services in food quality and food delivery services? The methodology used in this study uses a normative juridical approach, namely research that emphasizes the civil law literature and applicable legislation. Based on the discussion of the research results, it is concluded that: First, there are several regulations related to food service through the very strong grab application Second, regarding the lack of standardization given by Grab regarding food quality and there are still many shortcomings of legal regulations or legal certainty related to service food online